In-vitro antibacterial and anti-encrustation performance of silver-polytetrafluoroethylene nanocomposite coated urinary catheters. Issue 1 (September 2019) - Wang, L.; Zhang, S.; Keatch, R.; Corner, G.; Nabi, G.; Murdoch, S.; Davidson, F.; Zhao, Q.
Summary: Background: Catheter-associated urinary tract infections (CAUTIs) are among the most common hospital-acquired infections, leading to increased morbidity and mortality. A major reason for this is that urinary catheters are not yet capable of preventing CAUTIs. Aim: To develop an anti-infective urinary catheter. Methods: An efficient silver-polytetrafluoroethylene (Ag-PTFE) nanocomposite coating was deposited on whole silicone catheters, and two in-vitro bladder models were designed to test antibacterial (against Escherichia coli ) and anti-encrustation (against Proteus mirabilis ) performances. Each model was challenged with two different concentrations of bacterial suspension. Findings: Compared with uncoated catheters, coated catheters significantly inhibited bacterial migration and biofilm formation on the external catheter surfaces. The time to develop bacteriuria was an average of 1.8 days vs 4 days and 6 days vs 41 days when the urethral meatus was infected with 10 6 and 10 2 cells/mL, respectively. For anti-encrustation tests, the coated catheter significantly resisted encrustation, although it did not strongly inhibit the increases in bacterial density and urinary pH. The time to blockage, which was found to be independent of the initial bacterial concentration in the bladder, was extended from 36.2±1.1 h (uncoated) to 89.5±3.54 h (coated) following bacterial contamination with 10 3 cells/mL in the bladder. Moreover, the coated catheter exhibited excellent biocompatibility with L929 fibroblast cells. Conclusion: Ag-PTFE coated Foley catheters should undergo further clinical trials to determine their ability to prevent CAUTIs during catheterization.